STRATEGI BRANDING BIMBEL DALAM MEMBANGUN CITRA LEMBAGA PENDIDIKAN ALTERNATIF DI BIMBEL TIRTA EDUCATION GEMPOL - Nurul Firda; Wiwin Fachrudin Yusuf (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The increasingly rapid growth of nonformal educational institutions encourages every institution to develop effective branding strategies to create a positive image amidst fierce competition. Tirta Education Gempol Tutoring, as an alternative educational institution, strives to build its image through various branding strategies to attract public interest and strengthen the trust of students and parents. This study aims to analyze the branding strategy applied by Tirta Education Gempol Tutoring in building the image of an alternative educational institution. The approach used in this research is qualitative with a descriptive research type. The theoretical framework includes the Brand Equity Model by David A. Aaker, Brand Positioning by Al Ries and Jack Trout, Brand Identity Prism by Jean-Noël Kapferer, as well as alternative education theories from John Dewey, Paulo Freire, and Daniel Greenberg. The main research instrument is the researcher herself. Data collection techniques were carried out through passive participant observation, semi-structured interviews, and documentation. Data analysis employed the Miles and Huberman model consisting of data condensation, data display, and conclusion drawing. The findings reveal that Tirta Education Gempol Tutoring implements three integrated branding strategies, namely curriculum adaptation based on non-selective diagnostic tests, information transparency through weekly progress reports and monthly meetings with parents, as well as strengthening social values and inclusion through the "Free Tutoring for Underprivileged Children" program. These three strategies work synergistically to build brand equity, strengthen brand positioning in the public's mind, and create a robust brand identity. The theoretical implication of this study enriches the study of marketing management for nonformal education services by demonstrating that branding effectiveness for alternative educational institutions is not determined by luxurious facilities or massive promotions, but rather by the institution's ability to provide personalized, transparent, and inclusive learning solutions that align with the real needs of the community.